An empirical study of the relationships betwen corruption, capital leakages and country risk: part I - Bouchet, Michel (2006)
This paper investigates the relationship between corruption and capital flight in developing countries. Part I tackles the challenge of defining and measuring capital flight, as well as the various root causes of expatriated savings. Our research contributes to the corruption and capital market literature in several ways. First, the issue of capital flight has attracted less attention than that of external capital inflows in emerging market countries. In particular, capital flight has kept a low profile in academic circles until the late 1990s. In addition, research often looks at capital flight as a portfolio issue, and very few studies consider corruption as a «push factor». Second, our paper looks at why capital flight deserves renewed interest, as the globalization of financial markets broadens investment diversification opportunities for domestic residents. Increasingly, official agencies express concern regarding the recycling of generous development aid flows and heavy borrowing in the international capital markets outside the developing countries’ economies. In the aftermath of the G-7 1996 Cologne meeting, larger and broader debt relief, coupled with a strong emphasis on sustainable development policies, focuses on the urgency of capital flight repatriation. Third, we assume that corruption combines two kinds of centrifugal forces for capital leakages: corruption-driven money leaves a country because of fear of being caught by the tax and judiciary authorities; in addition, money leaves a country because of fear that a corrupt government will not provide a stable and conducive environment for safe savings and profitable investment. In Part II of our research, we test the assumption that the higher the level of corruption, the less conducive the national environment for private investment, and the greater the capital leakages.